Pedagogical Re-Orientation in the 21st Century and its Implications for Islamic Religious Education Learning - Nasrudin, Ega; Supriadi, Udin; Kosasih, Aceng; Abdussalam, Aam; Fakhruddin, Agus; Anwar, Saepul; Romli, Usup; Rahman, Roslan Abdur (Jurnal Iman dan Spiritualitas, 2025)
This research explores how the pedagogical orientation of the 21st century and its implications for IRE learning. The method used in this research is the literature study method. The results of this study reveal that the 21st century brings considerable changes in various aspects of life, including education. The main characteristic of this century is the rapid advancement of technology. These technological advances affect the way of learning, teaching, as well as the way of interacting in education. 21st-century learning emphasizes the achievement of critical thinking, collaboration, communication, and creativity skills (4Cs), as well as information literacy, technology, and life skills. In terms of pedagogical skills, it has shifted from traditional teacher-centered pedagogy to constructivist, learner-centered pedagogy. This pedagogical shift allows learners to actively build knowledge and skills through experience and technology. Learning strategies or methods that can be used in 21st-century learning include flipped classroom, experiential learning, problem-based learning, reflective learning, project-based learning, and inquiry learning. In the learning process, the teacher has an important role not as the only source of material but as a facilitator who creates an effective learning environment. In the context of Islamic Religious Education (IRE) learning, the relevance of 21st-century learning is applied through technology integration, emphasis on the achievement of 21st-century skills, the use of appropriate strategies, and a maximum evaluation process in accordance with the learning model used.